Recent advances in heme biocatalysis engineering - Schmitz, Lisa Marie; Rosenthal, Katrin; Lütz, Stephan (Technische Universität Dortmund, 2019)
Heme enzymes have the potential to be widely used as biocatalysts due to their capability to perform a vast variety of oxidation reactions. In spite of their versatility, the application of heme enzymes was long time‐limited for the industry due to their low activity and stability in large scale processes. The identification of novel natural biocatalysts and recent advances in protein engineering have led to new reactions with a high application potential. The latest creation of a serine‐ligated mutant of BM3 showed an efficient transfer of reactive carbenes into C═C bonds of olefins reaching total turnover numbers of more than 60,000 and product titers of up to 27 g/L−1. This prominent example shows that heme enzymes are becoming competitive to chemical syntheses while being already advantageous in terms of high yield, regioselectivity, stereoselectivity and environmentally friendly reaction conditions. Advances in reactor concepts and the influencing parameters on reaction performance are also under investigation resulting in improved productivities and increased stability of the heme biocatalytic systems. In this mini review, we briefly present the latest advancements in the field of heme enzymes towards increased reaction scope and applicability.
Biotechnology and bioengineering;116(12)
Keywords: Cytochrome P450 monooxygenases (P450s); Genomic data mining; Heme enzymes; Heme peroxidases; Peroxygenases; Protein engineering; 660